2022
DOI: 10.3389/fbioe.2022.796820
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Metal-Organic Framework Nanoparticles for Synergistic Combining of SDT-Chemotherapy Induce Pyroptosis in Gastric Cancer

Abstract: In recent years, sonodynamic therapy (SDT) has been widely developed for cancer research as a promising non-invasive therapeutic strategy. Here, we synthesized zeolitic imidazole frameworks-8 (ZIF-8) and utilized its properties to encapsulate hydrophobic Chlorin e6 (Ce6) and hydrophilic tirapazamine (TPZ) for a synergistic sonodynamic chemotherapy, which was also accompanied by the modification of cytomembrane of gastric cancer (GC) cells. Thus, we enabled the biomimetic property to achieve targeted delivery. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Moreover, the pyroptosis-related protein GSDMD may inhibit the cell proliferation of GC, and when GSDME is knocked down, the growth of GC cells is affected [ 132 , 133 ]. It is demonstrated that the release of ROS by sonodynamic therapy (SDT) treatment induces the pyroptosis of GC cells and plays the antitumor function [ 134 ]. It is reported that treating GC cells with famotidine triggers the activation of NLPR3 inflammasomes and leads to the mature and secretion of GSDME and IL-18, resulting in the pyroptosis of GC cells [ 135 ].…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…Moreover, the pyroptosis-related protein GSDMD may inhibit the cell proliferation of GC, and when GSDME is knocked down, the growth of GC cells is affected [ 132 , 133 ]. It is demonstrated that the release of ROS by sonodynamic therapy (SDT) treatment induces the pyroptosis of GC cells and plays the antitumor function [ 134 ]. It is reported that treating GC cells with famotidine triggers the activation of NLPR3 inflammasomes and leads to the mature and secretion of GSDME and IL-18, resulting in the pyroptosis of GC cells [ 135 ].…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…2 , porphyrins include hematoporphyrin (HP), protoporphyrin IX (PpIX), hematoporphyrin monomethyl ether (HMME), and chlorin e6 (Ce6). 63 As early as 1989, Yumita et al treated cell suspensions with hematoporphyrin as a sonosensitizer and then treated sarcoma cells and AH 130 cells with ultrasonic waves at a frequency of 1.92 MHz and different intensities. The results showed that HP combined with ultrasound damaged 99% and 95% of the tumor cells.…”
Section: Application Of Sonosensitizers In Sdtmentioning
confidence: 99%
“…Another study demonstrated that ZIF-8 outperformed the extensively used antibacterial ZnO ( Ahmed et al, 2019 ). The photoelectrons trapped within the zinc ions of ZIF-8 are responsible for ROS production inducing cell deformation and cytoplasm leakage of bacteria ( Ahmed et al, 2019 ; Li et al, 2022a ; Yu et al, 2022 ). It is noteworthy that the ZIF-8 crystal exhibits excellent capabilities for drug delivery because the ZIF-8 is stable in neutral or alkaline aqueous medium but break down rapidly in acidic medium ( Liu et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%